The Multifacets of COVID-19 in Adult Patients: A Concise Clinical Review on Pulmonary and Extrapulmonary Manifestations for Healthcare Physicians: Covid-19 and Pulmonary and Extrapulmonary Manifestations - Canatan , Duran; Vives Corrons, Joan Lluis; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
Summary. COVID-19 is an infectious disease caused by the SARS-CoV-2 virus. Most people with COVID-19 have a mild to moderate respiratory illness; others experience severe illness, such as COVID-19 pneumonia. The first and most accessible diagnostic information is from symptoms and signs from clinical examination. Infected patients present with a variety of manifestations. Formal diagnosis requires laboratory analysis of nose and throat samples, or imaging tests like CT scans. Emerging data suggest that coronavirus disease 2019 (COVID-19) has extrapulmonary manifestations. Sometimes these extra-respiratory manifestations may be the initial or only symptom of COVID-19, prior to fever or respiratory manifestations. In summary, our concise review shows that there is a wide range of symptoms that can be presented by COVID-19 patients. Extra-respiratory manifestations of SARS-CoV-2 infection have recently been observed in the rapidly increasing number of COVID-19 cases. Considering the broad spectrum of clinical manifestations and the increasing worldwide burden of the disease, there is an urgent need to rapidly scale up the diagnostic capacity to detect COVID-19 and its complications.